Kainate receptors in the hippocampus. (17th April 2014) - Carta, Mario; Fièvre, Sabine; Gorlewicz, Adam; Mulle, Christophe
Abstract Kainate receptors (KARs) consist of a family of ionotropic glutamate receptors composed of the combinations of five subunits, GluK1–GluK5. Although KARs display close structural homology with AMPA receptors, they serve quite distinct functions. A great deal of our knowledge of the molecular and functional properties of KARs comes from their study in the hippocampus. This review aims at summarising the functions of KARs in the regulation of the activity of hippocampal synaptic circuits at the adult stage and throughout development. We focus on the variety of roles played by KARs in physiological conditions of activation, at pre‐ and postsynaptic sites, in different cell types and through either metabotropic or ionotropic actions. Finally, we present some of the few attempts to link the role of KARs in the regulation of local hippocampal circuits to the behavioural functions of the hippocampus in health and diseases.